Edukasi Kepatuhan Minum Obat Anti Tuberkulosis terhadap Tingkat Kepatuhan Pasien Tuberkulosis Paru - Meidiana Putri; Satriani Satriani; Teti Hayati (Journal of Telenursing (JOTING), 2026)
This study aimed to determine the effect of education on adherence to anti-tuberculosis medication among pulmonary TB patients at the Pulmonary Clinic of Grogol Petamburan Community Health Center. The method used was a quasi-experimental design with a pre-test and post-test approach without a control group, involving purposively selected pulmonary TB patients. Education was provided through direct counseling and educational media, while adherence data were collected using questionnaires before and after the intervention. The results showed a significant increase in patient adherence after education. Patients who were previously less adherent showed behavioral changes by starting to take their medications regularly and on schedule. In conclusion, education significantly influenced adherence to anti-TB medication.   Keywords: Education, Adherence to Anti-Tuberculosis Medication (OAT), Pulmonary Tuberculosis